2007
DOI: 10.2106/jbjs.f.00290
|View full text |Cite
|
Sign up to set email alerts
|

Extracortical Bone-Bridging Fixation with Use of Cortical Allograft and Recombinant Human Osteogenic Protein-1

Abstract: In an animal model of segmental bone-replacement prosthetic fixation with use of the extracortical bone-bridging principle, an allogenic onlay cortical graft combined with rhOP-1 was an effective substitute for autogenous bone graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Analogous to BMP-2, BMP-7 has been employed in many large (baboon (Ripamonti et al, 2001a), dog (Fukuroku et al, 2007), goat (den Boer et al, 2002), monkey (Cook et al, 2002) and sheep (Cipitria et al, 2013)) and small (minipig (Warnke et al, 2006), mouse , rabbit (Haidar et al, 2010b) Success variability may be dosage dependent since direct administration of BMP-7 has ranged from 100 µg to 3.5 mg (Reichert et al, 2012;Ripamonti et al, 2000) in large animals (some studies employed 65 mg to 750 mg (Lind et al, 2001;Salkeld et al, 2001)) and 0.025 µg to 3.5 mg (Sampath et al, 1992;Warnke et al, 2006) in small animals. However, it remains to be ascertained whether this suggested correlation is positive (higher dose results in higher bone formation (Chen et al, 2006;Haidar et al, 2010b;Ripamonti et al, 2000)), negative (higher dose results in lower bone formation (Cook et al, 2005;Soballe et al, 2004)) or whether it indeed exists (bone formation remains unaffected by dosage (Hamdy et al, 2003;Leknes et al, 2008)).…”
Section: Direct Administration Of Bmp-7mentioning
confidence: 99%
“…Analogous to BMP-2, BMP-7 has been employed in many large (baboon (Ripamonti et al, 2001a), dog (Fukuroku et al, 2007), goat (den Boer et al, 2002), monkey (Cook et al, 2002) and sheep (Cipitria et al, 2013)) and small (minipig (Warnke et al, 2006), mouse , rabbit (Haidar et al, 2010b) Success variability may be dosage dependent since direct administration of BMP-7 has ranged from 100 µg to 3.5 mg (Reichert et al, 2012;Ripamonti et al, 2000) in large animals (some studies employed 65 mg to 750 mg (Lind et al, 2001;Salkeld et al, 2001)) and 0.025 µg to 3.5 mg (Sampath et al, 1992;Warnke et al, 2006) in small animals. However, it remains to be ascertained whether this suggested correlation is positive (higher dose results in higher bone formation (Chen et al, 2006;Haidar et al, 2010b;Ripamonti et al, 2000)), negative (higher dose results in lower bone formation (Cook et al, 2005;Soballe et al, 2004)) or whether it indeed exists (bone formation remains unaffected by dosage (Hamdy et al, 2003;Leknes et al, 2008)).…”
Section: Direct Administration Of Bmp-7mentioning
confidence: 99%
“…The expected standard deviation of 13 and effect size of 20% for the calculation were estimated from data on the use of OP-1 in canine acetabular defects [2]. Although biomechanical data for this type of model were not available at the time, a recent study showed a difference of 12% bone ingrowth in this model was associated with a 2.3-fold improvement in torsional stiffness and 2.2-fold maximum torque [17]. The calculation revealed that six animals would be required per group.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant human OP-1, also known as BMP-7, is one such growth factor with powerful osteoinductive properties [16] that enhances new bone formation and bone ingrowth [2,17]. Although one study proposed using autogenous corticocancellous onlay bone grafting at the bone-implant junction for superior bone formation, extracortical bone bridging, bone ingrowth, and soft tissue capsule formation around the prosthesis [47], others have proposed using growth factors with or without bone grafting to improve these processes [17,37,40]. A recent report indicates that cortical allograft used in combination with OP-1 in a canine model improves implant biomechanical stability in comparison to using autogenous bone grafting alone [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations